Anxiety, Anger and Depression Amongst Low-Income Earners in Southwestern Uganda During the COVID-19 Total Lockdown - Archibong, Victor; Usman, Ibe Michael; Kasozi, Keneth Iceland; Aigbogun, Eric Osamudiamwen; Josiah, Ifie; Monima, Ann Lemuel; Ssebuufu, Robinson; Chekwech, Gaudencia; Terkimbi, Swase Dominic; Owoisinke, Okon; Mbiydzenyuy, Ngala Elvis; Adeoye, Azeez; et al. (Frontiers in Public Health, 2021)
Background:Low-income earners are particularly vulnerable tomental health consequences of the COVID-19 lockdown restrictions, due to a temporary or permanent loss of income and livelihood, coupled with government-enforced measures of social distancing. This study evaluates the mental health state among low income earners Western Uganda and assesses their awareness of provision of mental healthcare during the first total Covid 19 lockdown in Uganda. Methods: A cross-sectional descriptive study was undertaken amongst earners whose income falls below the poverty threshold.Two hundred and fifty-three (n=253) male and female low-income earners between the ages of 18 and 60 years of age were recruited to the study. Modified generalized anxiety disorder (GAD-7), Spielberger’s State-Trait Anger Expression Inventory-2 (STAXI-2), and Beck Depression Inventory (BDI) tools as appropriate were used to assess anxiety, anger, and depression respectively among our respondents. Results: Severe anxiety (68.8%) followed by moderate depression (60.5%) and moderate anger (56.9%) were the most common mental health challenges experienced by low-income earners in Ishaka-Bushenyi Western Uganda. Awareness of mental healthcare increased with the age of respondents in both males and females. A linear relationship was observed between both age and depression (r= 0.154, P= 0.014)while positive correlations were observed between anxiety and anger (r= 0.254, P˂0.001); anxiety and depression (r= 0.153, P= 0.015) and anger and depression (r= 0.153, P= 0.015). Conclusion: The present study shows a relationship between age, sex, awareness, anxiety, anger, and depression among low-income earners, during the COVID-19 lockdown. Male respondents were more aware of the availability of mental health care, while female respondents were more affected by anxiety, depression, and anger.